2019
DOI: 10.1007/s13239-019-00445-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Resistance of Intracranial Flow-Diverter Stents: Measurement Description and Data Evaluation

Abstract: Purpose Intracranial aneurysms are malformations forming bulges on the walls of brain arteries. A flow diverter device is a fine braided wire structure used for the endovascular treatment of brain aneurysms. This work presents a rig and a protocol for the measurement of the hydrodynamic resistance of flow diverter stents. Hydrodynamic resistance is interpreted here as the pressure loss versus volumetric flow rate function through the mesh structure. The difficulty of the measurement is the very low flow rate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
(54 reference statements)
1
5
0
Order By: Relevance
“…found that although the porosity is a key factor in determining the flow reduction capability of the device, it is solely not sufficient [ 8 ]. We argue, as in our previous paper that the really decisive factor is the HR [ 21 ], of which the porosity is only one element. In this sense our findings complement those of Augsburger et al.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…found that although the porosity is a key factor in determining the flow reduction capability of the device, it is solely not sufficient [ 8 ]. We argue, as in our previous paper that the really decisive factor is the HR [ 21 ], of which the porosity is only one element. In this sense our findings complement those of Augsburger et al.…”
Section: Discussionsupporting
confidence: 71%
“…The geometrical data of the deployed devices were obtained using image processing techniques described in detail in Csippa et al. [ 21 ]. The deployed stents at the elliptical hole of the holder tube were photographed using a USB microscope (Dino-Lite, Torrance, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Our aim is to reproduce the flow diverter surface accurately, since this virtual stenting method is integrated with our CFD solution, 41 which uses a porous material description of the FD surface. The last component, the porous flow resistance of various flow diverter types is measured and discussed in Reference [42].…”
Section: Discussionmentioning
confidence: 99%
“…The apical surface of the endothelial cells is covered by the negatively charged endothelial glycocalyx and endothelial surface layer (ESL), which cover and floats into the lumen of the capillary vessels, and is a key player in the integrity of the glomerular filtration barrier. The endothelial glycocalyx and ESL consist of glycoproteins and proteoglycans covalently linked to the glucosaminoglycans heparan sulfate, chondroitin sulfate and hyaluronic acid [ 25 ]. The importance of the glycocalyx in homeostasis has progressively been recognized, due in part to its high charge selectivity restricting the passage of negatively charged molecules such as albumin [ 23 ].…”
Section: The Diabetic Milieu Affects Structure and Function Of Thementioning
confidence: 99%